THE USING OF FLASH INTERACTIVE MULTIMEDIA IN ISLAMIC EDUCATION COURSES TO IMPROVE SENIOR HIGH SCHOOL STUDENTS’ CONCEPTUAL UNDERSTANDING - Kuntoro, Rahmat; Supriadi, Udin; Asyafah, Abas (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
Delivery of materials, which is often uninteresting, is one of the main causes of students’ difficulties in understanding Islamic Education materials. The using of flash interactive multimedia in this course is a recent innovation in Islamic Education learning. Flash interactive multimedia has become a possible solution to present materials in a more interesting and meaningful way. Thus, the utilization of flash interactive multimedia is expected to aid students in understanding the concepts of Islamic Education materials. The aim of this study is to obtain an overview of improvement in students’ conceptual understanding, comparing those who are exposed to learning using interactive multimedia and those treated with conventional learning. The present study employs quasi- experiment method, using pre-test post-test control group design. The subjects are 25 students in the experiment class and 25 students in control class, selected through purposive sampling. Data is collected through students’ conceptual understanding test with multiple choices items. The findings show that conceptual understanding of students treated with flash interactive multimedia in Islamic Education lessons is higher than that of students treated with conventional learning. Students’ conceptual understanding improves significantly using interactive multimedia, compared to students’ conceptual understanding improvement in conventional learning.